2010
DOI: 10.1016/j.bpj.2010.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Two Kinesins Transport Cargo Primarily via the Action of One Motor: Implications for Intracellular Transport

Abstract: The number of microtubule motors attached to vesicles, organelles, and other subcellular commodities is widely believed to influence their motile properties. There is also evidence that cells regulate intracellular transport by tuning the number and/or ratio of motor types on cargos. Yet, the number of motors responsible for cargo motion is not easily characterized, and the extent to which motor copy number affects intracellular transport remains controversial. Here, we examined the load-dependent properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
225
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(248 citation statements)
references
References 34 publications
23
225
0
Order By: Relevance
“…Typically, a coated bead is attached to the motor [357,166]. The bead is placed in an optical trap, while the motor steps on a MT (Fig.…”
Section: Kinesin and Dynein Under Loadmentioning
confidence: 99%
“…Typically, a coated bead is attached to the motor [357,166]. The bead is placed in an optical trap, while the motor steps on a MT (Fig.…”
Section: Kinesin and Dynein Under Loadmentioning
confidence: 99%
“…In principle they can be determined experimentally by careful analysis of trajectories of two-motor complexes provided that the cargo states C 1 and C 2 can be identified. This approach has been taken in a series of recent studies by Diehl and collaborators, 34,48,53 who distinguish microstates with one or two load-bearing motors, although these do not necessarily correspond to the states C 1 and C 2 with one or two bound motors, if the motors do not share the load. Likewise, in gliding assays, trajectories can be partitioned into segments with one or two motor pulling the microtubule based on the different swiveling behavior of the microtubule.…”
Section: General Theoretical Frameworkmentioning
confidence: 99%
“…23 However, a recent study suggested that the load may not always be shared equally by the motors. 34 Finally, transport by multiple motors provides additional opportunities for the regulation of transport as illustrated by the effects of microtubule-associated proteins. 60,18 In recent years, it has therefore become more and more evident that to understand transport processes in cells, one has to move beyond single motors and study the cooperative action of several motors or motor assemblies and the mechanism by which these motors are coordinated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, investigators have designed in vitro experiments to limit the number of coupled motors so that mechanistic modeling efforts were tractable (8)(9)(10)(11). For these models, the velocity and direction of cargo transport generated by ensembles of antagonistic motors depended solely on the relative number of motors pulling in either direction (12,13).…”
mentioning
confidence: 99%